A model for assessment of heat and moisture transfer through hollow porous buildings elements. (September 2019) - Ayres de Mello, Luciano; Moura, Luis Mauro; Mendes, Nathan
Abstract: Moisture is one of the leading causes responsible for the worst of health conditions and energy performance in households and workplaces. To avoid it, the coupling between a combined heat, air and moisture (HAM) model and a CFD code becomes a crucial research topic to provide accurate results for real problems found in the building sector. Therefore, this paper presents a CFD-HAM model performed in one- and two-dimension simulations, displaying different results for each case. A comparison between one- and two-dimension heat and mass transfer migration through plaster and brick - with trapped air - is carried out, showing the potential of the proposed advanced modeling to solve complex heat and moisture transfer through building elements.